2021
DOI: 10.3389/fcvm.2021.746321
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Features and Protein Markers of Arrhythmogenic Cardiomyopathy

Abstract: Arrhythmogenic cardiomyopathy (ACM) is a heritable heart muscle disease characterized by syncope, palpitations, ventricular arrhythmias and sudden cardiac death (SCD) especially in young individuals. It is estimated to affect 1:5,000 individuals in the general population, with >60% of patients bearing one or more mutations in genes coding for desmosomal proteins. Desmosomes are intercellular adhesion junctions, which in cardiac myocytes reside within the intercalated disks (IDs), the areas of mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 101 publications
(137 reference statements)
2
7
0
Order By: Relevance
“…We further showed that mutant DSP p.Tyr1188His/WT cardiomyocytes exhibit lower levels of the gap junction protein CX43 and NaV1.5, which in turn may be causal for the observed prolongation of the action potential. These observations are in line with previous studies that demonstrated diminished CX43 and NaV1.5 levels in explanted cardiac material isolated from patients diagnosed with ACM ( Asimaki et al., 2009 ; Bueno-Beti and Asimaki, 2021 ; Jansen et al., 2012 ). In addition, studies revealed redistribution of CX43 to the long axis of cardiomyocytes upon desmosomal protein deficiency, which in turn may act as an arrhythmogenic substrate ( Bueno-Beti and Asimaki, 2021 ; Oxford et al., 2007 ; Zhang et al., 2013 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We further showed that mutant DSP p.Tyr1188His/WT cardiomyocytes exhibit lower levels of the gap junction protein CX43 and NaV1.5, which in turn may be causal for the observed prolongation of the action potential. These observations are in line with previous studies that demonstrated diminished CX43 and NaV1.5 levels in explanted cardiac material isolated from patients diagnosed with ACM ( Asimaki et al., 2009 ; Bueno-Beti and Asimaki, 2021 ; Jansen et al., 2012 ). In addition, studies revealed redistribution of CX43 to the long axis of cardiomyocytes upon desmosomal protein deficiency, which in turn may act as an arrhythmogenic substrate ( Bueno-Beti and Asimaki, 2021 ; Oxford et al., 2007 ; Zhang et al., 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…Molecular analyses of DSP p.Tyr1188His/WT hiPSC-derived cardiomyocytes revealed a reduction in desmosomal proteins, an observation previously reported in ventricular tissue obtained from patients with ACM ( Asimaki et al., 2009 ). Interestingly, this pathomolecular characteristic seems to be a hallmark of ACM, as it is not evident in other forms of cardiac disease ( Asimaki et al., 2009 ; Bueno-Beti and Asimaki, 2021 ). Besides reduced protein levels, we also observed lower mRNA levels for several components of the intercalated disc.…”
Section: Discussionmentioning
confidence: 98%
“…Pathological features of ACM include loss of myocytes and progressive fibro-fatty replacement. These pathological features tend to occur in the right ventricle (RV), with left ventricular (LV) or bilateral ventricular involvement [ 2 , 3 ]. Previous studies found that one or more mutations in genes encoding desmosomal proteins led to about 50% of ACM cases [ 4 ], including desmoglein2 (DSG2) [ 5 ], desmocollin2 [ 6 ], plakoglobin [ 7 ], desmoplakin [ 8 ], and plakophilin-2 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, ACM caused by mutations in desmosomal genes was associated with isolated or predominantly right ventricular disease (RV-ACM). However, recent studies have highlighted a high prevalence of left ventricular involvement along with isolated and left-dominant ACM forms (LV-ACM) in patients carrying FLNC , DSP , or DSG2 mutations, for instance [ 3 , 8 , 9 , 10 ].…”
Section: Arrhythmogenic Cardiomyopathymentioning
confidence: 99%
“…ACM is characterized by the fibrofatty replacement of the myocardium, typically progressing from the epicardium to the endocardium, and transmural fibrofatty infiltration can also be observed in advanced stages of the disease [ 1 , 4 , 5 , 6 , 10 , 18 ].…”
Section: Arrhythmogenic Cardiomyopathymentioning
confidence: 99%